School Feeding Programme and Academic Performance of Primary School Pupils in Southern Division Rukungiri Municipality. - Nimusiima, Lydia (Kabale University, 2024)
The purpose of the study is to examine the effect of the school feeding program on the academic performance of primary school pupils in the southern division of Rukungiri municipality. The study was guided by specific objectives, namely: identifying the impact of school feeding programs on the academic performance of pupils; studying the relationship between school feeding and pupil performance in primary schools; and comparing the academic performance of schools with school feeding programs and those without. The study utilized a cross-sectional research design utilizing both qualitative and quantitative data collection and analysis approaches. Using simple random and purposive sampling techniques, a total of 58 respondents were selected to participate in the study. Data was collected using questionnaires and key informant interviews. The majority of participants (94% agreed on the impact of the school feeding program on the academic performance of pupils, and the study found a significant positive relationship between the school feeding program and the academic performance of primary pupils in the southern division of Rukungiri municipality (p =0.01, r =.530**). This indicates that school feeding programs have a significant association with academic performance, and the majority of the respondents agreed that the education rate of pupils in a given school increased, unlike in schools where it did not. It was recommended that the school feeding policy be put in place and implemented to enforce the law and save starving